THE ANALYSIS OF THE INFLUENCE THE ECONOMY OF THE ATYRAU REGION ON THE ENVIRONMENT - L.N. Igaliyeva (Academic Journal of Physical and Chemical Sciences, 2019)
This article discusses the socio-economic development of Atyrau region, the priority areas of economic development of the region and its impact on the environment. Atyrau region is the largest oil and gas field in Kazakhstan. In the region’s economy energy, construction materials, agricultural and fishery industries are well developed. On this basis, new bases for sustainable development are being created: the social infrastructure improvement, the creation of new jobs, the maximal employment of local population, the preparation of qualified specialists. However, the region is named as the most ecologically unfavorable region in the country. The ecological situation in the region is formed by climate, anthropogenic factors and intensive development of oil and gas production. One of the global issues is the oil production wastes polluting the environment. In this regard, much attention is paid to solving this problem now. This is because the pollutants mentioned above, besides the environment harm a human body and lead to the various diseases. The article analyzes the effects of oil products on the environment, on the health of the population, and the current state of the Caspian Sea.